2018
DOI: 10.1111/jac.12285
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence and biomass of four cassava genotypes grown under rain‐fed upper paddy field conditions in the tropics

Abstract: Expanding the area under cultivation and increasing the productivity are two solutions to fulfil the high cassava demand. The objective was to determine the quantum efficiency of photochemistry, relative water content (RWC), growth and biomass of four cassava genotypes grown under rain‐fed upper paddy field conditions. The four cassava genotypes (Kasetsart 50, Rayong 9, Rayong 11 and CMR38–125–77) were evaluated under three environments in rain‐fed upper paddy field conditions in the Khon Kaen province, Thaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 20 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…The high photosynthetic capability of the leaf is of fundamental importance for more growth and storage root yield of cassava (El-Sharkawy et al, 1990;De Tafur, 2010). In addition to LGR during 120 to 180 DAP, quantum efficiency of photochemistry of Photosystem II of leaves may serve as a selection criterion to improve the efficiency of cassava yield trials, as Sawatraksa et al (2018) showed a significant relationship between this trait and storage root yield of cassava grown in upper paddy field during the rice off-season. A study from Phoncharoen et al (2019) with the same four cassava genotypes but under ) using a graphical approach for analyzing the genotype main effect plus genotype ´ environment interaction (G + GE) or GGEbiplot software (PC 1 and PC 2 are the first and second principal components, respectively; SVP is singular value partitioning).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high photosynthetic capability of the leaf is of fundamental importance for more growth and storage root yield of cassava (El-Sharkawy et al, 1990;De Tafur, 2010). In addition to LGR during 120 to 180 DAP, quantum efficiency of photochemistry of Photosystem II of leaves may serve as a selection criterion to improve the efficiency of cassava yield trials, as Sawatraksa et al (2018) showed a significant relationship between this trait and storage root yield of cassava grown in upper paddy field during the rice off-season. A study from Phoncharoen et al (2019) with the same four cassava genotypes but under ) using a graphical approach for analyzing the genotype main effect plus genotype ´ environment interaction (G + GE) or GGEbiplot software (PC 1 and PC 2 are the first and second principal components, respectively; SVP is singular value partitioning).…”
Section: Discussionmentioning
confidence: 99%
“…Pellet and El-Sharkawy (1993) and Pellet and El-Sharkawy (1997) reported that the growth rate of leaves is a fundamental cassava characteristic to enhance the formation of the leaf canopy, leaf area index, light interception, and canopy photosynthetic rate, and consequently high storage root yield and total biomass. In addition to LGR during 120 to 180 DAP, quantum efficiency of photochemistry of Photosystem II of leaves may serve as a selection criterion to improve the efficiency of cassava yield trials, as Sawatraksa et al (2018) showed a significant relationship between this trait and storage root yield of cassava grown in upper paddy field during the rice off-season. There are, therefore, various suggested criteria for cassava varietal selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oyetunji et al [12] reported the performances on chlorophyll fluorescence and biomass of two cassava genotypes (TMS 4(2) 1425 and TME1) grown under water stress for 3-6 months at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria. The data in terms of relative water content (RWC), chlorophyll fluorescence, and biomass for cassava genotypes were documented for growing in a greenhouse with water stress during the early growth stage [13] and for planting under rainfed conditions (water shortages between 2 to 6 months after planting) in upper paddy fields during the off-season of rice [14]. However, there is no evidence of physiological characteristics with respect to Pn, crop water status, chlorophyll fluorescence (Fv/Fm and Fv /Fm ), stomatal conductance, and water use efficiency (WUE) coupled with biomass and yield of other commercial cassava genotypes grown under rainfed upland conditions with limited water during a growth period, of high partitioning to storage root (9-12 months after planting) [15] in Thailand.…”
Section: Introductionmentioning
confidence: 99%